2004
DOI: 10.1097/01.asn.0000108971.98071.f2
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Albumin versus Saline for the Treatment of Intradialytic Hypotension

Abstract: Abstract. Intradialytic hypotension (IDH) is the most common complication of hemodialysis. Symptomatic IDH requires the administration of fluid and often results in the early termination of dialysis, both of which may prevent adequate fluid removal. The optimal fluid for the treatment of IDH remains unknown. A randomized, double-blind, crossover trial was performed in 72 chronic hemodialysis patients to determine whether 5% albumin was more effective than normal saline for the treatment of IDH. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…In stable as well as in cardiac-compromised HD patients blood volume was better preserved with albumin or hydroxyethyl starch in comparison with isotonic saline, whereas the efficacy of hydroxyethyl starch was comparable to albumin [46,47] . In a randomized crossover study in hypotensive-prone patients saline and albumin were equally effective in the treatment of hypotensive episodes [48] . Another study investigated the effects of hypertonic glucose solutions on blood volume as compared to iso-or hyperosmotic saline solutions in 6 stable HD patients and revealed that hypertonic glucose (20% glucose) resulted in a greater increase in blood volume than equal volumes of the other solutions [49] .…”
Section: Avoidance Of Sodium-containing Solutions To Treat Intradialymentioning
confidence: 99%
“…In stable as well as in cardiac-compromised HD patients blood volume was better preserved with albumin or hydroxyethyl starch in comparison with isotonic saline, whereas the efficacy of hydroxyethyl starch was comparable to albumin [46,47] . In a randomized crossover study in hypotensive-prone patients saline and albumin were equally effective in the treatment of hypotensive episodes [48] . Another study investigated the effects of hypertonic glucose solutions on blood volume as compared to iso-or hyperosmotic saline solutions in 6 stable HD patients and revealed that hypertonic glucose (20% glucose) resulted in a greater increase in blood volume than equal volumes of the other solutions [49] .…”
Section: Avoidance Of Sodium-containing Solutions To Treat Intradialymentioning
confidence: 99%
“…It is a major hindrance and has a negative impact on health-related quality of life in patients who are on the maintenance HD (2). Apart from patients' subjective discomforts, IHD often requires the early discontinuation of the dialysis session and/or the fluid replacement that results in chronic volume overload and underdialysis (3,4). Current guideline of the Dialysis Outcome Quality Initiative (DOQI) recommends that every effort be undertaken to minimize IHD that compromises the delivery of adequate dialysis (5).…”
mentioning
confidence: 99%
“…Decreased HRV, an indicator of suppressed autonomic activity that is associated with adverse clinical events and increased mortality in patients with stable ischemic heart disease and preserved left ventricular function [17], as well as in those with myocardial infarction [18,19], has also been associated with sudden death [20,21]. Our study revealed that there is (36.66%) of patients with chronic renal failure had hypotension episodes during the hemodialysis (table 3).…”
Section: Discussionmentioning
confidence: 81%
“…In uremia patients, increased plasma and tissue levels of catecholamine and resistance to their physiologic effect were reported by several authors [15,16,17].Clinical and laboratory evidence suggests that both B-adrenoreceptor and muscarinergic receptor -mediated responses are attenuated in the uremia state [18,19]. Furthermore, other endocrine and procaine systems that might affect sympathetic activity such as insulin release or the L-arginine-nitric oxide pathway are also impaired by renal insufficiency [20,21].…”
Section: Discussionmentioning
confidence: 99%